Evaluation of left and right ventricular myocardial function after lung resection using speckle tracking echocardiography. Issue 31 (August 2016) - Wang, Zhenhua; Yuan, Jianjun; Chu, Wen; Kou, Yuhong; Zhang, Xijun
Abstract : Abstract: The impact of major lung resections on myocardial function has not been well-investigated. We aimed to identify this impact through the use of speckle tracking echocardiography (STE) to evaluate the right and left ventricular myocardial function in patients who underwent lung resections. Thirty patients who had lung resections were recruited for this study. Ten patients who underwent pneumonectomies were matched by age and sex, with 20 patients who underwent lobectomies. STE was performed on both right and left ventricle (RV and LV). Strain values of pre and postlung resections were compared in both the pneumonectomy group and the lobectomy group. Comparison between the pneumonectomy group and the lobectomy group was also studied. Left ventricular ejection fraction remained normal (>55%), but significantly decreased after lung resection in both the pneumonectomy group and the lobectomy group. An accelerated heart rate was observed in both groups after lung resection, with the pneumonectomy group demonstrating extra rapid heart rate ( P < 0.05). Strain values in the RV and LV decreased in both groups after lung resection, with the pneumonectomy group exhibiting a further decrease in longitudinal strain in LV and RV when compared with the lobectomy group ( P < 0.05). Right and left ventricular dysfunction can occur after lung resection regardless of pneumonectomy or lobectomy, and lobectomy may have a less significant impact on myocardial functions. This study demonstrated that STE is able to detect acute cardiac dysfunction after lung resection.